2022
DOI: 10.3390/toxins14030184
|View full text |Cite
|
Sign up to set email alerts
|

Saporin as a Commercial Reagent: Its Uses and Unexpected Impacts in the Biological Sciences—Tools from the Plant Kingdom

Abstract: Saporin is a ribosome-inactivating protein that can cause inhibition of protein synthesis and causes cell death when delivered inside a cell. Development of commercial Saporin results in a technology termed ‘molecular surgery’, with Saporin as the scalpel. Its low toxicity (it has no efficient method of cell entry) and sturdy structure make Saporin a safe and simple molecule for many purposes. The most popular applications use experimental molecules that deliver Saporin via an add-on targeting molecule. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 181 publications
0
12
0
Order By: Relevance
“…Saporin is a potent and highly useful cell-killing agent for the development of IT therapies. Useful features of saporin include low cytotoxicity when not internalized (it lacks a cell-binding domain), strong cell-killing activity once internalized, molecular stability, resistance to chemical procedures, and the potential to produce saporin-ITs in yeast [ 52 , 53 ]. Consistent with our study, a previous study demonstrated that CD3-saporin is highly efficient in inducing cell death [ 96 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Saporin is a potent and highly useful cell-killing agent for the development of IT therapies. Useful features of saporin include low cytotoxicity when not internalized (it lacks a cell-binding domain), strong cell-killing activity once internalized, molecular stability, resistance to chemical procedures, and the potential to produce saporin-ITs in yeast [ 52 , 53 ]. Consistent with our study, a previous study demonstrated that CD3-saporin is highly efficient in inducing cell death [ 96 ].…”
Section: Discussionmentioning
confidence: 99%
“…We created a new murine CD3e IT (S-CD3e-IT) using the streptavidin–saporin (sZAP) conjugation system and analyzed saporin-induced VLS as a model protein toxin. Saporin toxins have been increasingly used in recent in vivo animal studies [ 52 , 53 ]. However, to date, the causal effects of saporin on VLS remain poorly investigated and somewhat controversial [ 54 , 55 , 56 ].…”
Section: Introductionmentioning
confidence: 99%
“…To assess the ability of the selected peptides to bind, internalize, and deliver a payload in the cytoplasm in RMS cells, we conjugated biotinylated peptides to the commercially available Streptavidin-ZAP, consisting of Saporin chemically conjugated to Streptavidin ( Figure 4 a). Saporin is a ribosome-inactivating protein first isolated from Sapinaria officinalis [ 49 ], which is useful to evaluate immunotoxin strategies and to delete specific cells in vivo [ 50 ]. Saporin depurinates a specific nucleotide in the ribosomal RNA 28S (A 4324 ), thus irreversibly blocking protein synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…The ‘Molecular Surgery’ technique [ 12 ] requires a targeting agent to specifically bind to a cell-surface molecule on the appropriate cell population. Specificity is usually provided by the targeting agent to a target.…”
Section: Introduction Of Streptavidin-saporin: Trade Name—streptavidi...mentioning
confidence: 99%
“…ATS was established to meet and augment the demand for targeted toxins. In the beginning, the market consisted mostly of neuroscientists who wanted to study specifically-lesioned neurons; these immunotoxins were appreciated and created new techniques, new careers, and new discoveries [ 12 ].…”
Section: Introduction Of Streptavidin-saporin: Trade Name—streptavidi...mentioning
confidence: 99%